(untitled) (The Pakistan Development Review, 2006)
Fiscal decentralisation is seen as a means to enhance the economic efficiency of the government and also promote economic growth. Fiscal decentralisation is the empowerment of fiscal responsibilities to the sub-national governments, involving devolution of powers to tax and spend along with arrangements for correcting the imbalances between resources and obligations. The effectiveness of fiscal decentralisation depends upon: (a) appropriate expenditure assignments—with division of functions among different levels of government depending upon their comparative advantage (called the principle of subsidiarity); (b) appropriate tax or revenue assignments; and (c) the efficient design of a system of transfers and its proper implementation [Kardar (2006)].